ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS INFORMASI LAPORAN KEUANGAN PEMERINTAH DAERAH - Rama Mahaputra, I Putu Upabayu; Putra, I Wayan (E-Jurnal Akuntansi; Vol 8 No 2 (2014), 2014)
Government institutions at this time , should further to improve the quality of financial performance in order to create accountability and transparency. One of its efforts is the delivery of the qualified government financial statements and appropriate of accounting standards that have been set . The purpose of this study was to determine the effect of human resource capacity, utilization of local financial information systems, internal control systems and the implementation of government accounting standards to the quality of financial reporting information in SKPD Gianyar regency . The used sampling method  is proportional stratified random sampling. Based on the analysis results, obtained that the human resource capacity, utilization of local financial information systems, internal control systems and the implementation of government accounting standards have a positive and significant effect to the quality of financial reporting information in SKPD Gianyar regency .
Keywords: human resources, financial information systems area, the system of internal control, government accounting standards, the quality of financial reporting information.